Implementation of Problem Based Learning to Improve The Quality of PAI Learning During The Covid-19 Pandemic at School: Implementasi Problem Based Learning Untuk Meningkatkan Kualitas Pembelajaran PAI Selama Pandemi Covid-19 di Sekolah - Siti Miftachul Ummah; Anita Puji Astutik (Academia Open, 2022)
This article aims to provide an explanation of the application of learning-based learning at SMPN 1 Gedangan, so that students at SMPN 1 Gedangan, especially class VII-E can more easily understand and absorb the subject matter delivered by PAI subject educators more easily. understanding and absorbing the subject matter delivered by PAI subject educators can be absorbed well despite learning to be brave at home during the covid-19 pandemic. The research approach used by the author is descriptive qualitative research. Where the research subjects are PAI subject educators (Pak Abdul Mujib) and class VII-E students at SMPN 1 Gedangan. The data collection technique used by the author uses interview, observation, and documentation techniques.